Charles C. Marshall papers - Marshall, Charles C.
Correspondence, writings, notes, newspaper clippings, scrapbooks, and other papers relating primarily to Marshall's controversy in 1927 with Alfred E. Smith over the qualifications of a Roman Catholic for the presidency of the United States. Subjects include church-state questions, religious freedom, the Calvert controversy in seventeenth-century Maryland, and Marshall's book, The Roman Catholic Church in the Modern State (1928). Correspondents include E. Boyd Barrett, Frederic R. Coudert, Frank Courtenay Dodd, James M. Gillis, L.H. Lehmann, Walter Lippmann, Arthur Selden Lloyd, Wilfrid Parsons, and Michael Williams.
Lawyer. Full name: Charles Clinton Marshall. Born 1860; died 1938.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Barrett, E. Boyd -- 1883- -- Correspondence; Baltimore, Charles Calvert, -- Lord, -- 1637-1715.; Coudert, Frederic R. -- 1871-1955 -- Correspondence; Dodd, Frank Courtenay, -- 1875-1968 -- Correspondence; Gillis, James M. -- 1876-1957 -- Correspondence; Lehmann, L. H. -- 1895-1976 -- Correspondence; Lippmann, Walter, -- 1889-1974 -- Correspondence; Lloyd, Arthur Selden, -- 1857-1936 -- Correspondence; Parsons, Wilfrid, -- 1887-1958 -- Correspondence; Smith, Alfred Emanuel, -- 1873-1944.; Williams, Michael, -- 1878-1950 -- Correspondence; Calvert family; Catholic Church; Church and state; Freedom of religion; Presidents -- United States -- Election -- 1928.; Maryland -- History -- Colonial period, ca. 1600-1775; Lawyers